Rare Metastasis of Gastric Cancer to the Thyroid Gland: A Case Report and Review of Literature - Wu, Zehui; Guo, Tao; Li, Qiang; Cheng, Liang; Hu, Xiaosi; Xu, Aman (Frontiers in Surgery, 2021)
Abstract Background It is common for patients with gastric cancer to develop distant metastases in liver, lung, bone, or brain. However, detection of metastases in the thyroid is uncommon despite the rich vasculature of the thyroid. Due to the rarity, the clinical features of this condition are not well established. Here, we present a case of thyroid metastasis of gastric cancer treated in our hospital. Case Summary This case report refers to a 63-year-old female with a mass in the anterior neck and mild hoarseness for 6 months. The patient underwent proximal subtotal gastrectomy because of Siewert III esophagogastric junction cancer 6 years ago. After that, she received 8 cycles of adjuvant chemotherapy. Her condition was quiet well until 6 month ago, when a mild hoarseness developed for no apparent reason. Both ultrasonography and computed tomography confirmed a heterogeneous mass in the right lobe of thyroid gland. Blood thyroid function test and tumor markers were normal. Suspected of medullary thyroid carcinoma, she underwent right thyroidectomy, and during operation the tumor was found invading right recurrent laryngeal nerve and trachea. H&E staining and immunohistochemistry suggested that the cancer cells originated from gastric cancer. The patient was diagnosed with thyroid metastasis of gastric cancer. She refused further treatment and died in the next 6 month. Conclusion The metastatic thyroid tumor of gastric cancer is rare and shows poor prognosis. This condition must be considered in the differential diagnosis of thyroid nodules. Immunohistochemical diagnosis is essential for conclusive diagnosis of it.